1994
DOI: 10.1002/food.19940380204
|View full text |Cite
|
Sign up to set email alerts
|

Winter season krill (Euphausia superba D.) as a source of n‐3 polyunsaturated fatty acids

Abstract: Krill (Euphausia superba D.) caught in winter near South Georgia were examined as a raw, intermediate product, precipitate and by product. The following assayes were performed: lipid composition (TLC), fatty acid composition (GC), lipid susceptibility to oxidation, and carotenoids content. The krill harvested in July/August was found to contain about 3% of lipids. The amount of n‐3 polyunsaturated fatty acids (PUFA; eicosapentaenoic and docosahexaenoic acids) in total lipids of whole krill accounts for 19.0 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 17 publications
3
30
1
Order By: Relevance
“…Yoshitomi and Nagano (2012) reported 15.6% palmitic acid and 16.5% oleic acid, similar to values observed in our study, although their EPA content (7.8%) was lower than that observed our study. Kolakowska et al (1994) also showed a similar result for EPA and DHA, while Cho et al (1999) reported that palmitic acid, EPA, and DHA were found at levels of 19.95, 16.14, and 14.09%, respectively, in the lipids from whole krill powder. Sriket et al (2007) reported DHA and EPA at levels of 14.9 and 8.58%, respectively, in the lipids from black tiger shrimp order of concentration from highest to lowest.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Yoshitomi and Nagano (2012) reported 15.6% palmitic acid and 16.5% oleic acid, similar to values observed in our study, although their EPA content (7.8%) was lower than that observed our study. Kolakowska et al (1994) also showed a similar result for EPA and DHA, while Cho et al (1999) reported that palmitic acid, EPA, and DHA were found at levels of 19.95, 16.14, and 14.09%, respectively, in the lipids from whole krill powder. Sriket et al (2007) reported DHA and EPA at levels of 14.9 and 8.58%, respectively, in the lipids from black tiger shrimp order of concentration from highest to lowest.…”
Section: Resultssupporting
confidence: 54%
“…Previous studies have shown that krill had a moisture content of 77.9-83.1%, lipid content of 0.4-3.6%, protein content of 11.9-15.4%, and chitin content of <2% (Grantham, 1977), although one study recorded a protein content of 72.9-75.8% (dry matter) and lipid content of 12-50% (dry matter; Saether et al, 1986;Jaczynski et al, 2011). Krill oil contains a high volume of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA; Kolakowska et al, 1994;Jaczynski et al, 2011). Krill have a higher proportion of cholesterol than fish but less than shrimp , containing 123 μg/g zinc (Zn; dry matter), 2.5 μg/g cadmium analyzed according to the method of Horwitz (2005).…”
Section: Introductionmentioning
confidence: 99%
“…Krill is a small marine crustacean (2.5-6-cm size and 2-g weight) whose 65 % of total dry weight are proteins and, depending on the species, age, and time from capture to freezing, the lipid content varies from 12 to 50 % (Kolakowska et al 1994;Saether et al 1986;Svetlova et al 1985). Most of the commercially available krill are harvested in the Antarctic Ocean (Euphausia superba).…”
Section: Introductionmentioning
confidence: 99%
“…Suzuki and Shibata [4] reported that the biological value of krill proteins was higher than that of other meat protein and milk proteins. It is abundant in omega-3 polyunsaturated fatty acids (n-3 PUFA), for example eicosapentaenoic (EPA, 20:5n3) and docosahexaenoic (DHA, 22:6n3) acids [7]. Gigliotti et al [8] proved that oil extracted from krill contained predominantly phospholipids (20-33%), polar nonphospholipids (64-77%), and minor triglycerides (1-3%).…”
Section: Introductionmentioning
confidence: 98%